Garden as environmental intervention in restoration process of hospitalized children - Said, Ismail; Salleh, Siti Zaleha; Abu Bakar, Mohd. Sarofil (Faculty of Built Environment, UTM, 2004)
This study investigates the psychological benefits attained by pediatric patients after experiencing a hospital garden during their restoration process. The benefits are measured from patients’ increased cognitive performances, improved performance tasks and increased social performances when they play or rest in the garden. Thirty-one patients, aged 6 to 12 years, from the pediatric ward of Batu Pahat Hospital are allowed to experience the garden and their behavioral responses are elicited through field observations by the investigator and caregivers. The responses are measured in two ways: (1) qualitative i.e. preference and satisfaction of patients to the garden properties and attributes by semi-structured interview, and (2) quantitative i.e. movement of patient in play activities by behavioral mapping. It is found that 81% (n=25) patients preferred to be in the garden than the ward. Their preferences are influenced by 11 properties or attributes of the garden including refreshing smell, fresh air, full with light, cheerful environment, pleasant sound, scenic view, open space, free to play, not confined, home feeling, and place for variety of activities. Moreover, 68% (n=21) of patients played actively in the garden with long length of play (mean=52 minutes) and high to moderate number of equipment played (11 to 25 equipment). Such behavioral responses suggest the garden fosters the patients’ restorative process by increasing their functioning: cognitive, physical and social. This finding suggests the importance to include garden as an environmental intervention to enhance the health recovery of the pediatric patients in the hospital setting.